Filamentous fungi found on foundress queens of leaf-cutting ants (Hymenoptera: Formicidae) - Rodrigues, André [UNESP]; Silva, A.; Bacci Junior, Mauricio [UNESP]; Forti, Luiz Carlos [UNESP]; Pagnocca, Fernando Carlos [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
Queens of the leaf-cutting ant species Atta laevigata and Atta capiguara were collected soon after their mating flight and maintained in the laboratory until death. Ant corpses showing signs of contamination by insect pathogenic fungi were selected for fungal identification. Filamentous fungi such as Beauveria bassiana and Paecilomyces lilacinus actively sporulated in the ant's corpses. This is the first report of the latter fungus on reproductives of leaf-cutting ants. The fact that queens may acquire filamentous fungi including saprophytic and potential insect pathogens after their mating event is especially interesting regarding the impacts of such microbes on the establishment of a new nest.
Keywords: Atta; Beauveria; Paecilomyces; Entomopathogens; Mating flight; Microfungi